The Effects of Fiscal Policy on Employment Stability in Uganda: A Case Study of the Ministry of Finance, Planning and Economic Development (MOFPED) - Nathan Mwebesa (Uganda Christian University, 2024)
The study established the effects of fiscal policy on employment stability in Uganda: acase study of Ministry of Finance, Planning, and Economic Development. It specifically focused on; examining the relationship between taxation and job creation in Uganda, finding out the relationship between public investments and unemployment in Uganda and examining the relationship between government spending and labor force participation in Uganda. The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and simple random sampling methods were used. A sample size of 44 respondents who are management and employees from MOFPED was also used in the study. The data was anlysed using Chi-square statistics with the help of SPSS version 20. From the study findings using chi-square statistics highlight the intricate interplay between taxation, public investments, government spending, and their impact on job creation and labor force participation in Uganda. While taxation is perceived as a deterrent to job creation, it was majorly revealed that there’s optimism regarding the potential of tax policy reforms, especially in reducing payroll taxes, to positively influence employment. Therefore, it can majorly be concluded that taxation, public investment and government spending have a great impact on employment stability in Uganda. Lastly, the study recommended a multi-pronged approach to improve Uganda’s employment situation. This includes tax breaks for businesses to encourage job creation, along with increased government spending in key areas like education, healthcare, and technology.